Young trendsetters: How young voters fuel electoral volatility. (February 2022) - Rekker, Roderik
Abstract: Sociological theory posits that social change occurs first and foremost among young people, who set trends that may eventually carry over to older citizens. This study examined to what extent this proposition applies to electoral shifts by comparing parties' electoral gains among young (age <25) and older voters (age >24) in 21 Western established democracies between 1948 and 2019. An analysis of 219 national election surveys revealed that winning parties typically gained disproportionately among young voters. This youth bonus was even stronger for new parties, whose electoral breakthroughs were importantly facilitated by youths. Electoral shifts among young voters furthermore predicted similar changes among older citizens in the subsequent election. This indicates that young people are not only more sensitive to electoral trends, but that they can also set trends that eventually carry over to older citizens. Young voters should therefore be seen as important drivers of electoral volatility.